2021
DOI: 10.1093/trstmh/trab072
|View full text |Cite
|
Sign up to set email alerts
|

Global scientific research progress in mycetoma: a bibliometric analysis

Abstract: Background Mycetoma is a neglected tropical disease that attracts little attention in regard to research and publications and hence this study was undertaken to determine the trends and global scientific research output in mycetoma-related fields. Methods Mycetoma data were retrieved from the Web of Science (WoS) and Scopus databases. The MeSH Browser was used to extract relevant keywords. Biblioshiny software (R-studio cloud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Therefore, the actual prevalence and incidence figures are unknown. In 2021, a bibliometric analysis estimated that, in the last 23 years worldwide, only about 20 articles per year have been published about this disease 13 . As a result, studies on the causal agent of actinomycetoma are also scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the actual prevalence and incidence figures are unknown. In 2021, a bibliometric analysis estimated that, in the last 23 years worldwide, only about 20 articles per year have been published about this disease 13 . As a result, studies on the causal agent of actinomycetoma are also scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, bibliometric analysis help identifies hot research topics and research gaps in the field. Global, regional, and country-level research on NTDs as a group or as a specific NTD showed an increasing trend [ 26 – 28 ]. In this context, the author did a bibliometric analysis of research publications on NTDs in which at least one author is based in the Arab region to assess the extent of contribution of researchers in the Arab region to the field which can be used for future health planning, research funding, and establishing new research collaborations.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of non-steroidal anti inflammatory drugs or oral prednisolone may improve clinical outcomes [4 ▪ ]. Despite an increase in attention to this neglected condition, significant progress needs to be done [10].…”
Section: Introductionmentioning
confidence: 99%